Singapore’s embrace of shareholder stewardship: A puzzling success - PUCHNIAK, Dan W. (Institutional Knowledge at Singapore Management University, 2022)
The United Kingdom’s idea to adopt a stewardship code sparked a global shareholder stewardship movement. Unsurprisingly, Singapore as a corporate governance leader in Asia, adopted a stewardship code. Based on a superficial textual analysis, the Singapore Code appears to be a near carbon copy of the UK Code. However, this Article, which provides the first in-depth comparative analysis of stewardship in Singapore, demonstrates how Singapore has turned the UK model of stewardship on its head. Rather than enhancing the shareholder voice of institutional investors, shareholder stewardship has been used in Singapore as a mechanism for entrenching its successful state-controlled and family-controlled system of corporate governance. This development has been entirely overlooked by prominent international observers and would be beyond the wildest imaginations of the original architects of the UK Code. Viewed through an Anglo–American lens, this use of “stewardship” may suggest that Singapore has engaged in a corporate governance sham. However, this Article argues the opposite: it appears to be a secret to Singapore’s continued corporate governance success and provides a much-needed Asian (as opposed to Anglo–American) model of good corporate governance for Asia.